2012
DOI: 10.21161/mjm.04012
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Aloevera barbedensis, Daucus carota, Emblica officinalis, Honey and Punica granatum and Formulation of a Health Drink and Salad

Abstract: Aims: Indian folk medicine has been in practice from time immemorial. Traditional medicine interconnects our body with nature for a healthy living. The naturally occurring antimicrobials in food vary in their efficacy and function, toxicology, safety and mechanism of action against microorganisms. Methodology and Results:The study revitalizes the traditional system of medicine in order to achieve self reliance in health care and health for all by analyzing the antimicrobial property of aqueous extracts of aloe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Especially, plant secondary metabolites are highly appreciated and have already been reported in prodigious claims, i.e., antioxidant, antimicrobial, anticancer properties, etc. (Golechha et al, 2012; Philip et al, 2012; George et al, 2016; Muniyandi et al, 2017). Also, plant secondary metabolites are reported as potential candidates for biogenic production of nanoparticles and the method was highly satisfactory and being termed as green synthesis tactic (Akhtar et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, plant secondary metabolites are highly appreciated and have already been reported in prodigious claims, i.e., antioxidant, antimicrobial, anticancer properties, etc. (Golechha et al, 2012; Philip et al, 2012; George et al, 2016; Muniyandi et al, 2017). Also, plant secondary metabolites are reported as potential candidates for biogenic production of nanoparticles and the method was highly satisfactory and being termed as green synthesis tactic (Akhtar et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Emblica officinalis is also known as Phyllanthus emblica , which belongs to the family Phyllanthaceae and genus Phyllanthus , whose edible fruits are widely used in Indian Ayurvedic medicine (Dharmananda, 2003). There are abundant benefits of E. officinalis , which include, antibacterial (Philip et al, 2012), antifungal (Mehmood et al, 1999), antioxidant and cardioprotective activities (Golechha et al, 2012). The E. officinalis fruits are a rich source of hydrolyzable phenolics, flavonoids, and tannins that play a key role in reducing and regulating the shape of nanoparticles (Ankamwar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] In another study on Aloe vera , the serial dilution method revealed that a high concentration (1/10) inhibited the growth of Staphylococcus aureus at, while moderate concentrations were required to inhibit the growth of Escherichia coli , Pseudomonas aeruginosa , and Salmonella typhi . [ 29 ] Another study was conducted to determine the antimicrobial activity of Aloe vera juice against Gram-positive bacteria and Gram-negative bacteria, and the results showed that the antibacterial activity of the tested plant juice was effective mainly against the Gram-positive bacteria. [ 30 ] An experiment was performed to analyze antimicrobial activities against S. aureus , S. pyogenes , P. aeruginosa , and E. coli , and it was observed that the maximum antibacterial activities were noticed in the acetone extract other than the aqueous extract or the ethanol extract.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits are an important part of human diet that provides essential nutrients as well as many bioactive compounds like vitamins and secondary metabolites for promotion of health and prevention of diseases (Liu, 2013). Recently immense interests among the scientists have grown to find the antimicrobial properties of fruits of human consumption (Bansode and Chavan, 2013;Das, 2012;Manzoor, 2013;Philip et al, 2012;Rahman et al, 2015;Khan and Hanee, 2011). In this present study an attempt was made to investigate the antimicrobial activities of the juices of some edible Citrus and non Citrus fruits against some medically important gram positive and gram negative bacteria.…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 725-731mentioning
confidence: 99%